2019
DOI: 10.3390/plants8100426
|View full text |Cite
|
Sign up to set email alerts
|

Do No Harm: Efficacy of a Single Herbicide Application to Control an Invasive Shrub While Minimizing Collateral Damage to Native Species

Abstract: Control of invasive exotic species in restorations without compromising the native plant community is a challenge. Efficacy of exotic species control needs to consider collateral effects on the associated plant community. We asked (1) if short-term control of a dominant exotic invasive, Lespedeza cuneata in grassland restorations allows establishment of a more diverse native plant community, and (2) if control of the exotic and supplemental seed addition allows establishment of native species. A manipulative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In contrast to this study, some short-term studies showed that the non-target vegetation was degraded by herbicide application. For example, Gibbson et al 19 showed that the phylogenetic diversity of the community became lower due to single herbicide treatment. Szitár and Török 20 also showed that the single herbicide spraying of common milkweed disturbed the vegetation, and it modified the succession to an earlier initial state.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this study, some short-term studies showed that the non-target vegetation was degraded by herbicide application. For example, Gibbson et al 19 showed that the phylogenetic diversity of the community became lower due to single herbicide treatment. Szitár and Török 20 also showed that the single herbicide spraying of common milkweed disturbed the vegetation, and it modified the succession to an earlier initial state.…”
Section: Discussionmentioning
confidence: 99%
“…For example, herbicide treatment can be more efficient when assimilates translocate to the roots in the late summer, as reported in several studies on other invasive clonal plants [110,111]. However, the substances and the treatment's halflife must be considered in protected areas, and a break of at least 1 year between treatments is advisable to allow regeneration of natural vegetation [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of established invasive species, the most successful options are eradication or isolation [8][9][10][11][12][13]. Herbicide treatment is one of the most effective ways to control or eradicate invasive plants in large areas [10,[14][15][16][17][18][19]. Nevertheless, the prevention and control measures of invasive species with chemicals are rather arguable whereas their use endangers other species and the ecology and abiotic elements (above and below ground waters, soil and air) in protected areas [18,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations